GENETIC VARIATION IN PHOSPHORUS DEFICIENCY TOLERANCE AMONG BANGLADESHI RICE (ORYZA SATIVA L.) CULTIVARS AND INTROGRESSION LINES WITH IR 64 GENETIC BACKGROUND - M. N. Uddin; S. Hilton; Y. Fukuta; M. Z. Hossain; S. M. M. K. Khan (Journal of Animal and Plant Sciences, 2023)
Phosphorus is vital nutrient for the crop yield, and Breeding rice for tolerant to low phosphorus, efficient in uptake and assimilation is the best way for sustainable production. This study aimed to evaluate Bangladeshi rice cultivars and introgression lines under phosphorus deficient soil to understand the genetic variation in deficiency tolerance. A total of 28 rice genotypes from various ecotypes such as Aus, Aman, Boro and Jhum were collected and grown in pot contained highly phosphorus deficient soil in the rooftop polythene shed house during October 2019 to March 2020. A phosphorus deficiency susceptible variety, IR 64, was used as control, and experiment was conducted following randomized complete block design with two replications. Biomass related traits such as dry weight (DW) and relative dry weight (RDW, %) were analyzed at early vegetative stage. Visual score based on the responses to artificial drought occurred appeared due to absence of water for 5 consecutive days because of government imposed Covid-19 lockdown were also evaluated in a scale of 0 to 4. Plants showed wide variation in the measured traits in both in the phosphorus added normal or phosphorus deficient conditions. Two patterns of responses were observed. One pattern was similar to susceptible control IR 64 and another is highly sensitive to P- deficiency. Cluster analysis resulted four groups (I to IV). Group I consist of four rice varieties including Pathar kuchi, Lal dhan, INL-9, and INL-30, and showed low DW and low tolerances to phosphorus deficiency and artificial drought. Group II had nine accessions including IR 64, Murali, Kuti Agrani, Kernaicha, and five INLs. They had higher DW and susceptible to phosphorus deficiency and artificial drought. Group III had medium DW and susceptible under phosphorus deficient condition and Kali jira and Aus (Awned) are included. Two jhum variety, Renkhoa Dhan and Galongpru, and seven INLs are belong to the group IV which has also had medium RDW and tolerant to phosphorus deficient and artificial drought. The genetic variations of DW and RDW under the conditions of phosphorus deficient and artificial drought were clarified rice varieties in Bangladesh and INLs with IR 64 genetic background, and several varieties and INLs were found as the promising materials for further breeding program for them.
Keywords: genetic variation; Phosphorus deficiency tolerance; rice; Relative Dry weight